Economic Development Zones Empowering Regional Economies for High Quality Development Pathway Studies — Take L Economic Development Zone in City D as an Example - Yang Zhang (Journal of World Economy, 2024)
Since the reform and opening up, China’s economic development zones have developed at a high speed. As the experimental field and pacesetter of reform and opening up, development zones play an extremely important role in China’s economic and social development. In particular, it has made great contributions to optimizing industrial institutions, developing foreign trade, increasing regional taxes and other aspects. As a fast lane for China’s economic development, the industrialization of development zones is the essential feature of development zones. Under the market economy, development zones play an important engine role in the country’s industrialization and modernization. As the experimental field of urban economic development and the representative of location policy orientation, economic development zones also play an important role in the high-quality development of regional economy in China. At present, China’s economic development is facing the demand of iterative transformation and upgrading. Developing new quality productivity and promoting the good development of production relations have become an important development task at present and in the future. As a pilot area, the economic development zone has a huge effect on the improvement of regional economic quality. This paper takes the economic development zone of L District as an example to build a case analysis mechanism framework based on the perspective of political economy, study how economic development zones can enable high-quality development of regional economy.